Stripping Voltammetry Microprobe (Spv): A New Approach in Electroanalysis - Paez-Collio, M; Paez-Collio, M; Zagal-Moya, J; Zagal-Moya, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Azocar-Guzman, M; Azocar-Guzman, M; Vera-Oyarce, C; Vera-Oyarce, C; Tamayo-Villarroel, L; Tamayo-Villarroel, L; et al. (2014)
This paper describes how electrochemical trace analysis can be performed in micro samples based on the precipitation of a sparingly soluble compound and its immobilization on an electrode surface. Precipitation is performed in a solution droplet put on the electrode in an upside-down position in air. The solvent of the droplet is then evaporated and the immobilized residue is subjected to a voltammetric measurement after introducing the electrode to an electrolyte solution. This methodology can be used for the quantification of dissolved ions (after precipitation) as well as for that of dispersed solids. As example, here the quantification of silver ions following precipitation as AgCl is described. © 2014 Elsevier B.V.